2014
DOI: 10.1016/j.rmed.2013.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary rehabilitation improves long-term outcomes in interstitial lung disease: A prospective cohort study

Abstract: NCT01055730 (clinicaltrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
129
3
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(148 citation statements)
references
References 36 publications
8
129
3
8
Order By: Relevance
“…This was previously demonstrated among COPD and ILD patients, suggesting greater improvement in longer pulmonary rehabilitation programs [7,10], and supported by Kozu et al [33], who showed that the dyspnea severity and disability level of IPF patients at baseline has a negative impact on the degree of improvement following pulmonary rehabilitation. In contrast, Huppmann et al [34] and Ryerson et al [35] showed higher improvement rates in 6MWD following pulmonary rehabilitation programs in the most deconditioned ILD patients and those with low baseline values, respectively [34,35]. Our findings are also in concordance with a recent report by Arizono et al [36], who also showed significant improvements of CPET parameters in IPF patients, but not V O 2 peak.…”
Section: Discussionsupporting
confidence: 92%
“…This was previously demonstrated among COPD and ILD patients, suggesting greater improvement in longer pulmonary rehabilitation programs [7,10], and supported by Kozu et al [33], who showed that the dyspnea severity and disability level of IPF patients at baseline has a negative impact on the degree of improvement following pulmonary rehabilitation. In contrast, Huppmann et al [34] and Ryerson et al [35] showed higher improvement rates in 6MWD following pulmonary rehabilitation programs in the most deconditioned ILD patients and those with low baseline values, respectively [34,35]. Our findings are also in concordance with a recent report by Arizono et al [36], who also showed significant improvements of CPET parameters in IPF patients, but not V O 2 peak.…”
Section: Discussionsupporting
confidence: 92%
“…Such benefit was assessed using the 6MWT, with an average gain of 70 meter before and after PR. This outcome is on a par with the minimal clinically important difference (MCID) in other chronic disease states, such as 54 meter in COPD 20 or 56-57 meter seen in patients with interstitial lung disease 16,21 or 25 meter in patients with coronary artery disease. 22 Our intention was to evaluate and compare the outcomes in pharmacotherapy and PR in PH and also compare it to newer data that supports an MCID of 33 meters for patients with PH.…”
Section: Summary Of Main Findingsmentioning
confidence: 98%
“…Early referral to physical training should be considered, as less severe physiological limitation may provide greater opportunity to successfully undertake training [52]. But several studies found that patients with very low functional exercise capacity and severe symptoms should be offered the opportunity to undertake a training program and may experience clinically important benefits [1,73].…”
Section: Physical Training In Sarcoidosismentioning
confidence: 99%